2017
DOI: 10.1016/j.athoracsur.2016.08.073
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Gastrointestinal Bleeding After Sutureless Aortic Valve Replacement: A Word of Caution

Abstract: We report the clinical case of a male patient who presented, after an aortic valve replacement with a rapid deployment bioprosthesis, a Heyde-like syndrome, secondary to a moderate aortic paravalvular leakage. All the digestive and hematologic investigations confirmed the diagnosis. A redo surgery to fill the paravalvular gap was accomplished and the postoperative course was uneventful, with a normalization of the biological parameters. To our knowledge, this is the first described case of such a complication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…We summarized the remaining 34 articles of case reports following aortic valve intervention in patients with Heyde's syndrome, with special references to angiodysplasia and HMW multimers of VWF (Table 1). To the best of our knowledge, there were seven reports that demonstrated persistence or disappearance of angiodysplasia after aortic valve intervention 10,11,16,30,31,35,41) . Importantly, although gastrointestinal bleeding ceased after aortic valve intervention in many case reports, followup endoscopic images to confirm the presence or absence of angiodysplasia and alterations of HMW patients with severe AS 5) .…”
Section: Discussionmentioning
confidence: 99%
“…We summarized the remaining 34 articles of case reports following aortic valve intervention in patients with Heyde's syndrome, with special references to angiodysplasia and HMW multimers of VWF (Table 1). To the best of our knowledge, there were seven reports that demonstrated persistence or disappearance of angiodysplasia after aortic valve intervention 10,11,16,30,31,35,41) . Importantly, although gastrointestinal bleeding ceased after aortic valve intervention in many case reports, followup endoscopic images to confirm the presence or absence of angiodysplasia and alterations of HMW patients with severe AS 5) .…”
Section: Discussionmentioning
confidence: 99%
“…The authors reported no further episodes of gastrointestinal bleeding with normalization of HMW vWF multimer as summarized in Table 2. Although these findings were not replicated in a few case reports [54,55], most of the evidence available in the literature has proven AVR to be more effective.…”
Section: Aortic Valve Replacementmentioning
confidence: 87%
“…All patients recovered well during the follow-up, except 5 patients who developed various complications. One patient [15] had perivalvular leakage after AVR followed by gastrointestinal bleeding, and the second AVR with biological valve stopped the bleeding. Gastrointestinal bleeding of 2 patients recurred.…”
mentioning
confidence: 99%